Implementation of Entrepreneur Kids Program with Traditional Gresik Snacks (Pudak) in Developing Early Childhood’s Social-Emotional - Ubaidillah, Ubaidillah; Chasana, Indi Muti’atul; Arisanti, Nur Albania; Lisanda, Nahdhiyatul Fitri; Ilmiyah, Nur Hidayatul (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to describe: Implementation of the Entrepreneur Kids Program with Gresik Traditional Snacks (Pudak) to Develop Social Emotional Skills in Early Childhood. This type of research is qualitative research with a descriptive method. Data sources come from primary data, which is data received directly by researchers and secondary data is complementary or supporting data related to the research. Data collection techniques are observation, interviews, documentation. Data analysis techniques are data collection, data reduction, data presentation, and drawing conclusions. Data validity testing uses triangulation of sources, techniques and time. The results of this study indicate that entrepreneur kids activities with traditional snacks to develop social emotions in early childhood can increase insight into Gresik local culture, one of which is introducing pudak, as well as gaining experience in learning how to make pudak and developing social emotions in children, especially being able to be responsible for completing activities from start to finish.